The Application of Teaching Media by Using Google Computer Science First for English Vocabulary - Amri Raya Duran, Yulkifli; Qalbi, Nur; Sangkala , Ismail (Journal of Computer Interaction in Education, 2019)
This research aims to find out (1) how to apply Google CS First for English vocabulary learning and (2) how are the students respond by using Google CS First in English vocabulary learning. This is a qualitative descriptive research, while the instruments used in this research are field notes and observation checklists, from the results of the research it is known that for the application of Google CS First itself there are 19 steps which are divided into two stages, the first is the preparation stage, this is the stage where the teacher made English vocabulary learning media using Google CS First. the next stage is the implementation stage, where the learning media that has been created using Google CS First is applied in the classroom. Furthermore, students' responses to the use of Google CS First gave a positive response, judging from the results of the first day of learning that did not use Google CS First, from the six aspects of activity observed, five of them showed a poor response, but on the second day of observation where learning was using Google CS First, the 6 aspects observed showed a fairly possitive response, and it can be concluded that Google CS First is the right learning media to make students more enthusiastic in participating in learning